PELAKSANAAN SUPERVISI KEPALA SEKOLAH SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM PEMBUATAN ADMINISTRASI PEMBELAJARAN DARING DI SMK NEGERI CIPATUJAH - ANTON SUSANTO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
A teacher should ensure a learning process is carried out well and achieves learning objectives. The problems encountered at the SMK Negeri Cipatujah at this time are how the implementation of learning during the Covid-19 pandemic can be effective and efficient, the existing teacher problem is in the preparation of the syllabus, the components in the syllabus are not filled out completely and clearly, the learning materials are only written only names only books, the method is not written down, the learning steps are not clear, the evaluation used is not available, and the motivation and apperception used by the teacher is not clear. The lesson plan prepared by the teacher is not in accordance with what is carried out when learning in class, especially during the COVID-19 pandemic. The formulation of the problem in this study is whether there is an increase in the ability of teachers in making learning administration or the completeness of online learning tools with the implementation of the supervision of the Principal at Cipatujah State Vocational School for the 2020/2021 Academic Year. Furthermore, the purpose of this school action research is to find out the improvement of teachers’ abilities in making learning administration or the completeness of online learning tools through the supervision of the Principal at SMK Negeri Cipatujah for the 2020/2021 Academic Year. The research method used is the School Action Research method, because the research is conducted to solve the problem of the learning process in schools. This study describes how a School Action Research technique is implemented at SMK Negeri Cipatujah. The conclusions are 1) there is an increase in the ability of teachers in making learning administration or completeness of online learning tools. The results of pre-action coaching on the ability of teachers to make online learning tools complete, it was found that teachers still had difficulty in making learning administration or online learning tools complete because so far learning still requires classrooms as a face-to-face place, implementation of learning during the pandemic requires teachers to use applications so that students can use it online, while teachers in using online applications are also still learning and a weak internet network is one of the obstacles to implementing learning during this pandemic. 2) Through the supervision of the Principal at the SMK Negeri Cipatujah for the 2020/2021 academic year, the teacher’s ability to make online learning tools has increased significantly. If in the first cycle the total average value of the teacher’s competence only increased from the first cycle, namely the percentage of completeness 66.67% and 88.89% in the second cycle the teacher was generally said to be complete with the total increase in the teacher’s average score was 8.67 and the total percentage increase is 22.22%, this shows the improvement efforts made by researchers in the second cycle bring changes. Academic supervision is effectively used to increase teacher competence at SMK Negeri Cipatujah in making online learning tools. 3) Teacher activities show that coaching activities through academic supervision are useful and can help teachers at SMK Negeri Cipatujah improve their pedagogical competencies.